2003
DOI: 10.1046/j.1462-2920.2003.00442.x
|View full text |Cite
|
Sign up to set email alerts
|

An immunomagnetic separation–reverse transcription polymerase chain reaction (IMS‐RT‐PCR) test for sensitive and rapid detection of viable waterborne Cryptosporidium parvum

Abstract: The public health problem posed by the waterborne parasite Cryptosporidium parvum incited the water supply industry to develop very accurate analytical tools able to assess the presence of viable oocysts in drinking water. In this study, we report the development of a viability assay for C. parvum oocysts based on immunomagnetic separation and reverse transcription polymerase chain reaction (IMS-RT-PCR). The detection limit of the IMS-RT-PCR assay, which targets the hsp70 heat shock-induced mRNA, was in the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 28 publications
0
21
1
Order By: Relevance
“…Other more recent approaches utilize molecular biology-based techniques to assess oocyst viability. Fluorescence in situ hybridization (5,10,20,26,40,47), nucleic acid sequence-based amplification (4), reverse transcriptase PCR (RT-PCR) (17,22,50), and an integrated cell culture/ PCR assay (12,25) all show promise in providing a rapid and relatively inexpensive viability assay for Cryptosporidium. However, it still remains to be determined if these methods can detect all Cryptosporidium species and genotypes found in the environment.…”
mentioning
confidence: 99%
“…Other more recent approaches utilize molecular biology-based techniques to assess oocyst viability. Fluorescence in situ hybridization (5,10,20,26,40,47), nucleic acid sequence-based amplification (4), reverse transcriptase PCR (RT-PCR) (17,22,50), and an integrated cell culture/ PCR assay (12,25) all show promise in providing a rapid and relatively inexpensive viability assay for Cryptosporidium. However, it still remains to be determined if these methods can detect all Cryptosporidium species and genotypes found in the environment.…”
mentioning
confidence: 99%
“…Previous studies indicate a 1,000-to 10,000-fold increase in the amount of HSP70 mRNA recovered from Drosophila species under heat stress (14). Second, HSP70 mRNA is a good indicator of oocyst viability; only viable oocysts will produced HSP70 mRNA by the use of heat shock (9,19). Third, previous studies suggest that the half-life of HSP70 mRNA (ϳ50 min) extracted from human cell lines (HeLa and 283 cells) is increased at least 10-fold upon heat shock, suggesting the increased stability of the targets (21).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, more recent efforts have been concentrated on reverse transcriptase PCR (RT-PCR) detection of mRNA, which degenerates more quickly than rRNA (35). Several targeted genes have been used, including the ␤-tubulin, hsp70, amyloglucosidase, and CP2 genes (18,22,27,35). A current challenge is the improvement of sensitivity of RT-PCR detection protocols.…”
Section: Meeting Reviews Eukaryot Cellmentioning
confidence: 99%
“…A current challenge is the improvement of sensitivity of RT-PCR detection protocols. Although the detection limit of one viable oocyst was achieved in initial studies, much higher limits (10 to 1,000 viable oocysts per sample) were reported subsequently (22,27,35), and in at least one instance, the decay of mRNA to below limits of detection preceded the loss of oocyst infectivity in cell culture and mouse models (26). Others have used nucleic acid sequence-based amplification of Cryptosporidium mRNA in assessments of the viability of oocysts in water samples (12).…”
Section: Meeting Reviews Eukaryot Cellmentioning
confidence: 99%